PRUNING AND PACLOBUTRAZOL INDUCED VIGOUR, FLOWERING AND HORMONAL CHANGES IN MANGO (MANGIFERA INDICA L.) - V. SRILATHA,; Y. T. N. REDDY,; K. K. UPRETI,; S. JAGANNATH, (The Bioscan, 2015)
A study was conducted to evaluate the effects of pruning (current or previous season’s vegetative growth) and paclobutrazol (PBZ @3 ml/m canopy diameter) on tree vigour, flowering and hormonal contents of three mango varieties, Raspuri, Dashehari and Amrapali differing in their bearing habits. Trees pruned to current season’s growth and with application of PBZ recorded 62, 52 and 61.5% lesser plant height, 50.2, 27.3 and 35.3% lesser trunk girth and 51.5, 45.8, 35.3% lesser canopy spread, 39.6, 35.2 and 26.5% decline in shoot length, 23.7, 19.0 and 14.9% decline in shoot girth and 20.4, 13 and 14.7 days advanced fruit harvesting followed by unpruned trees with PBZ application in the cvs Raspuri, Dashehari and Amrapali respectively compared with control. Trees pruned to current season’s growth and with PBZ application recorded decline in gibberellin (GA3) contents and increase in abscisic acid (ABA) levels at 45 and 75 days after PBZ application compared to control. From the study, it was apparent that the pruning of trees to current season’s growth and PBZ application are beneficial for regulating tree size, early flowering and advancing fruit harvest in mango and such effects are mediated through increase in ABA and decrease in GA3 contents.